Effect of Different Microbial Treatments on Germination, Seedling Growth and Other Quality Parameters of Maize (Zea mays L.) - Dr. Anurag Titov, Azad Ahmad Wani, (Journal of Medical Biomedical and Applied Sciences, 2016)
The cultivated species âZea mays L.â belongs to family poaceae (Graminae) which is the fifth largest family consisting of 10,000 species and at least 600 genera, unquestionably the most important family providing majority of food. In the present study, the experiment pro-tray method was conducted at Krishi vigyan Kendra (KVK) Ujjain (M.P.) to find out the possible effects of different microbial seed treatments includes Phosphorus solubilizing bacteria (PSB), Trichoderma viride and Azatobacter on seed germination, seedling length, vigour index and its contributing characters and subsequent seed quality parameters of maize. These microbial inoculants were thoroughly mixed with compost @ 15g/Kg compost before sowing. Results of the study showed that all treatments significantly enhanced seed germination, seedling length, Seedling vigour, chlorophyll content and leaf area of maize. The highest germination percentage (83.8%), Shoot length (25.8%), Root length (10.1%), total seedling length (35.3cm), seedling dry weight (0.27mg), Seedling vigour index SV-I (3429 mg), Vigour index SV-II (26.3mg), Leaf area (16.35 cm2) and Chlorophyll content like Chl. a, Chl. b and Total chl. (0.4948 mg/g, 0.4521 mg/g and 0.9466mg/g) and other parameters were obtained in seeds treated with Phosphorus solubilizing bacteria (PSB) followed by Azatobacter and Trichoderma viride. Hence, the results suggested that seeds treated with these microbial treatments can be considered as efficient alternative bio-fertilizers to promote better seed quality in terms of germination percentage, shoot length, Root length, seedling length, seedling dry weight, vigour index, leaf area and chlorophyll content.